Answer: 2) 26 4) -22 6) 28 8) -12
Explanation:
Replace the variable with its given value.
Then use PEMDAS to evaluate the expression.
Parenthesis
Exponents
Multiplication, Division
Addition, Subtraction
2) 5y - 3z + 4y - 1z - 3y ; y = 3, z = -2
5(3) - 3(-2) + 4(3) - 1(-2) - 3(3)
= 15 - (-6) + 12 - (-2) - 9
= 15 + 6 + 12 + 2 - 9
= 26
4) -k² - (3k - 5n) + 4n ; k = -1, n = -2
-(-1)² - [3(-1) - 5(-2)] + 4(-2)
= - 1 - [ -3 - (-10)] + (-8)
= -1 - ( 3 + 10) - 8
= -1 -13 - 8
= -22
6) 3(2c + d) - d ; c = 5, d = -1
3[2(5) + (-1)] - (-1)
= 3( 10 - 1) + 1
= 3(9) + 1
= 27 + 1
= 28
8) 4(2m - n) - 3(2m - n) ; m = -15, n = -18
4[2(-15) - (-18)] - 3[(2(-15) - (-18)]
= 4( -30 + 18 ) - 3( -30 + 18 )
= 4( -12) - 3(-12)
= -48 + 36
= -12